rWTC-MBTA Vaccine Induces Potent Adaptive Immune Responses Against Glioblastomas via Dynamic Activation of Dendritic Cells - Wang, Herui; Medina, Rogelio; Ye, Juan; Zhang, Yaping; Chakraborty, Samik; Valenzuela, Alex; Uher, Ondrej; Hadrava Vanova, Katerina; Sun, Mitchell; Sang, Xueyu; Park, Deric M; Zenka, Jan; et al. (Advanced science (Weinheim, Baden-Wurttemberg, Germany), 2024)
Despite strides in immunotherapy, glioblastoma multiforme (GBM) remains challenging due to low inherent immunogenicity and suppressive tumor microenvironment. Converting "cold" GBMs to "hot" is crucial for immune activation and improved outcomes. This study comprehensively characterized a therapeutic vaccination strategy for preclinical GBM models. The vaccine consists of Mannan-BAM-anchored irradiated whole tumor cells, Toll-like receptor ligands [lipoteichoic acid (LTA), polyinosinic-polycytidylic acid (Poly (I:C)), and resiquimod (R-848)], and anti-CD40 agonistic antibody (rWTC-MBTA). Intracranial GBM models (GL261, SB28 cells) are used to evaluate the vaccine efficacy. A substantial number of vaccinated mice exhibited complete regression of GBM tumors in a T-cell-dependent manner, with no significant toxicity. Long-term tumor-specific immune memory is confirmed upon tumor rechallenge. In the vaccine-draining lymph nodes of the SB28 model, rWTC-MBTA vaccination triggered a major rise in conventional dendritic cell type 1 (cDC1) 12 h post-treatment, followed by an increase in conventional dendritic cell type 2 (cDC2), monocyte-derived dendritic cell (moDC), and plasmacytoid dendritic cell (pDC) on Day 5 and Day 13. Enhanced cytotoxicity of CD4+ and CD8+ T cells in vaccinated mice is verified in co-culture with tumor cells. Analyses of immunosuppressive signals (T-cell exhaustion, myeloid-derived suppressor cells (MDSC), M2 macrophages) in the GBM microenvironment suggest potential combinations with other immunotherapies for enhanced efficacy. In conclusion, the authors findings demonstrate that rWTC-MBTA induces potent and long-term adaptive immune responses against GBM.
Keywords: Tumor Microenvironment; Immunity; nádorové mikroprostředí; immunotherapy; Glioblastoma; vakcíny; dendritic cells; rWTC‐MBTA vaccine; imunita; Mice; glioblastom; Dendritic Cells; CD8-pozitivní T-lymfocyty; dendritické buňky; zvířata; Vaccines; glioblastoma; tumor microenvironment; myši; CD8-Positive T-Lymphocytes; Animals